Molecularly resolved mapping of heterogeneous ice nucleation and crystallization pathways using in-situ cryo-TEM - Zibing Wang; Zifeng Yuan; Mouyang Cheng; Xudan Huang; Keyang Liu; Yihan Wang; Huacong Sun; Lei Liao; Zhi Xu; Ji Chen; Wenlong Wang; Lei Liu; et al. (Nature Communications)
Abstract Crystallization plays a fundamental role in diverse fields such as glaciology, geology, biology, and materials science. Among various crystallizing systems, the formation of ice remains elusive, despite decades of intensive investigation. In this study, we integrate in-situ cryogenic transmission electron microscopy with molecular dynamics simulations to develop a molecular-resolution mapping and thermodynamic framework for deposition freezing under low-temperature, low-pressure conditions. Our results demonstrate that ice formation on rapidly cooled substrates, representing far-from-equilibrium states, proceeds via an adsorption-mediated, barrierless pathway of heterogeneous ice nucleation, followed by progression toward thermodynamic equilibrium. This process is unveiled to involve a series of distinct yet interconnected steps, including amorphous ice adsorption, spontaneous nucleation and growth of ice I, Ostwald ripening, Wulff construction, oriented coalescence, and aggregation, all governed by interfacial free energy minima. Our findings offer direct molecular-level insight into the mechanisms of heterogeneous ice nucleation, enrich current understanding of non-classical nucleation pathways, and emphasize the critical role of interfacial energetics in shaping ice crystal morphology and quality.